2015
DOI: 10.1097/md.0000000000002205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Deep Vein Thrombosis in Patients Undergoing Lumbar Interbody Fusion Surgery

Abstract: This cross-sectional study was designed to obtain the current prevalence of deep vein thrombosis (DVT) and analyze related risk factors in patients undergoing lumbar interbody fusion.Medical record data were collected from Department of Spinal Surgery, The Third Hospital of Hebei Medical University, between July 2014 and March 2015. Both univariate analysis and binary logistic regression analysis were performed to determine risk factors for DVT.A total of 995 patients were admitted into this study, including 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Johnson et al 28 demonstrated increased odds of composite thrombotic events equal to 1.104 per RBC unit (95% CI 1.032-1.194, P = .0035). Similarly, Yang et al 41 reported that large blood transfusions were associated with increased rates of postoperative DVT in lumbar fusion patients ( P = .04). The only inconclusive report among these studies was limited by a small rate of events (3 in 160 patients).…”
Section: Resultsmentioning
confidence: 84%
“…Johnson et al 28 demonstrated increased odds of composite thrombotic events equal to 1.104 per RBC unit (95% CI 1.032-1.194, P = .0035). Similarly, Yang et al 41 reported that large blood transfusions were associated with increased rates of postoperative DVT in lumbar fusion patients ( P = .04). The only inconclusive report among these studies was limited by a small rate of events (3 in 160 patients).…”
Section: Resultsmentioning
confidence: 84%
“…Yang et al 5 revealed that the DVT incidence was 17% (147/861 patients) after spinal surgery, including fusion and nonfusion surgery. However, they reported in another study 10 that the rate of lower limb DVT detection by ultrasonography was 22.4% (223/995) in patients who underwent lumbar interbody fusion; the same authors reported 2 different results regarding the incidence of lower limb DVT. Perhaps they performed different surgical procedures for various spinal diseases, such as cervical spondylopathy, thoracic diseases, and lumbar disc degenerative diseases, which were evaluated together.…”
Section: Discussionmentioning
confidence: 96%
“…The major acquired factors include malignancy, recent major surgery, prior thrombotic event, pregnancy, oral contraceptives, hormone replacement therapy, immobilization, antiphospholipid antibody syndrome, and myeloproliferative disorders [32]. Blood transfusion might have an effect on thromboembolic disease, for example; red blood cell (RBC) and platelet transfusions are associated with an increased risk of venous and arterial thrombotic events and mortality only in hospitalized cancer patients and postoperative procedures [33, 34]. Each unit of fresh frozen plasma (FFP) increased VTE risk by 25% in patients who required less than 4 units of RBC.…”
Section: Discussionmentioning
confidence: 99%